أثر إدمان الأباء على الكحول في انتشار العدوانية لدى الأبناء - حطابي, الصادق (جامعة الوادي - University of Eloued, 2023)
يعتبر إدمان الكحول لدى أرباب الأسر، من المشكلات الاجتماعية التي تؤثر مباشرة على أفراد الأسرة، فنجد عائلات تفككت، وأطفال شردوا وأموال أهدرت، نتيجة دخول هذا الإدمان الأسر. وإن الإدمان على الكحول عند الآباء، قد يؤثر على الأطفال وهم أجنة في بطون أمهاتهم، بما تتعرض له الأم، من انفعالات غير سارة، تحت تأثير كافة صور الإيذاء الذي تتعرض له الأم، من طرف زوجها المدمن، ويتعدى تأثير هذه الظاهرة الى حالات تفكك أسري، يؤدي إلى تشرد الأبناء وحرمانهم من عطف الأبوين ورعايتهما، او اكتسابهم سلوكات عنيفة ناتجة عن الجو الأسري العام، ومن اجل تبيان مخاطر هذه الظاهرة تعمنا في دراستنا اجراء تحقيق ميداني لعينة من الآباء المدمنين على الكحول والذين حاولنا من خلالهم استخلاص مجموعة من النتائج التي تنجر عن إدمان الاباء للكحول، وخاصة التي تمس بشكل مباشر أسرهم و سلوكات أبنائهم، وأكدت النتائج أن أغلب المدمنين يعانون عدم قدرتهم على رقابة أبنائهم، حيث أن الأسرة التي يكون الأب فيها مدمن كحول يسودها النزاع والشجار الدائم بين الوالدين، ويلجأ فيها الوالدين إلى استعمال أساليب تربوية خاطئة كاستعمال العقوبة الجسدية والتهديد، والإهمال والطرد كأساليب لضبط السلوك فيهربون من المنزل ومن المدرسة، مما يدفع الأطفال الى تقليد نفس الأسلوب المنتهج داخل الآسرة وبذلك نكون وفرنا جو مناسب لإنتاج العنف وهو ما سنتعرف عليه في هذه الدراسة. Abstract: Alcohol addiction among heads of families is one of the social problems that directly affect family members . And alcohol addiction among fathers may affect children while they are fetuses in their mothers’ wombs, as the mother is exposed to unpleasant emotions, under the influence of all forms of abuse to which the mother is exposed, by her addicted husband, and the effect of this phenomenon goes beyond cases of family disintegration. , leads to the homelessness of children and depriving them of the kindness and care of their parents, or their acquisition of violent behavior resulting from the general family atmosphere. Parents’ addiction to alcohol, especially that directly affects their families and their children’s behavior, and the results confirmed that most addicts suffer from their inability to control their children, as the family in which the father is an alcoholic is dominated by conflict and constant quarrel between parents, and parents resort to using wrong educational methods such as using Corporal punishment, threats, neglect and expulsion as methods to control behavior, so they flee from home and from school, which leads children to imitate the same method used within the family and thus we provide an appropriate atmosphere for the production of violence, which is what We will learn about it in this study
مقال
Keywords: إدمان ؛ كحول ؛ أباء ؛ عنف ؛ أبناء; addiction; Alcohol ; fathers; violence; sons.